Development and psychometric characteristics of analog measures of parental empathy - Samantha Gonzalez (Public Library of Science (PLoS), 2021)
Despite substantial literature on the effect of empathy on parenting, empathy research has historically suffered from definitional and methodological limitations. Parental empathy can be characterized as parents’ ability to recognize, take the perspective of, and appropriately react to children’s emotions. Current parental empathy assessment largely relies on self-report measures of dispositional empathy, but many argue parental empathy is distinct from dispositional empathy. Despite efforts to measure parental empathy implicitly, such analog approaches are labor intensive. The current report describes the preliminary development of the Empathy Measure for Parents Analog Task (EMPAT), two novel analog measures of parental empathy: one EMPAT analog uses audio stimuli and a second version uses written evocative scripts. After piloting with a sample of undergraduate students (Study 1), the measures were then administered to a sample of 212 parents (Study 2). For each study, the accuracy of the audio and script stimuli were first confirmed by examination of frequency distributions, then exploratory factor analyses were conducted to determine factor structure for each emotion subscale (i.e., Happy, Mad, Sad, Scared), and finally the composition of each emotion subscale was confirmed with scale reliability analyses. Correlations between each EMPAT version and measures of dispositional empathy, parental empathy, and positive parenting indicators were examined to assess the initial validity of the EMPAT measures. The new analog tasks demonstrated good reliability as well as preliminary evidence of validity, with potential utility in assessing cognitive elements of empathy in particular. With continued efforts to examine measure validity, the implications of these studies suggest the EMPAT tasks show promise in providing improved implicit, efficient assessments of child-directed empathy, which may be important for understanding positive and problematic parenting.